(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
The "King of Spices," Piper nigrum, is one of 75 spice varieties cultivated in India. Adi pepper, a farmer's variety registered with the Protection of Plant Varieties and Farmers' Rights (PPVFR) Authority, was compared with P. nigrum based on its phytochemical, antioxidant, and antibacterial activities. Despite comparable phytochemical screening, Adi pepper ethanolic extract had greater total phenolic and flavonoid content (30.66±0.13 mg GAE/g DCE and 43.08±0.04 mg QE/g DCE). In antioxidant analyses, Adi pepper ethanolic extract exhibited a lower IC50 value in the 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) assay (IC50 = 85.14±0.12) compared with P. nigrum (IC50 = 94±0.12). Reducing ability was also higher in Adi pepper ethanolic extract (0.431±0.00) compared to P. nigrum (0.254±0.00) in the reducing power assay. Adi pepper ethanol extract also presented a greater inhibition zone against S. typhi (18±0.00 mm) and lower Minimum Inhibitory Concentration (MIC) values (0.625 mg/mL) among tested pathogens. Gas Chromatography-Mass Spectrometry (GC-MS) analysis identified antimicrobial, anti-inflammatory, and insecticidal alkaloids as well as amide-type alkaloids in both types. Both peppers, in general, showed antioxidant and antibacterial activity, but Adi pepper slightly more, perhaps due to specific phytoconstituents. Further investigation of such bioactive components could enhance their culinary, medicinal, and other applications.